The Influence of Hedonic Shopping Motivation and Perceived Ease of Use on Impulse Buying in Generation Z Shopee Users in Pondok Melati District - Stafrezar, Burhan (Lafadz Jaya Publisher, 2024)
The rapid development of Shopee means that businesspeople must be careful in determining the right strategy to attract the attention of consumers, especially Gen Z. Therefore, sellers on the Shopee application need to know the factors that influence impulse buying, two of which are hedonic shopping motivation and perceived ease. of use. The data used in this research is primary data obtained from a sample of 100 generation Z SPaylaters in Pondok Melati sub-district. The analysis used in this research uses multiple linear regression analysis with the SPSS version 25 program. The results of this research show that partially hedonic shopping motivation has a positive and significant effect on impulse buying among Generation Z Shopee users in Pondok Melati District. Partially perceived ease of use has no effect on impulse buying among Generation Z Shopee users in Pondok Melati District. The independent variables hedonic shopping motivation (X1) and perceived ease of use (X2), together have a positive and significant effect on impulse buying (Y) in Generation Z Shopee users in Pondok Melati District.